Analysis of the Zakat Management of the National Amil Zakat Agency (BAZNAS) in Asahan Regency - Novita Sari; Muhammad Arif (Journal of Indonesian Management, 2022)
This article aims to describe the management of zakat in the National Amil Zakat Agency (BAZNAS) of Asahan Regency. This article is a type of empirical and descriptive research conducted at the National Amil Zakat (BAZNAS) of Asahan Regency. In collecting primary data sources, researchers used the interview method, while for secondary data collection researchers used the documentation method. Based on the results of the study, zakat in the BAZNAS of Asahan Regency has been managed properly and has complied with sharia provisions, so that zakat funds in Asahan Regency can be felt by the community in accordance with the goals of the prescribed zakat. The zakat collected comes from zakat maal on agricultural products, commercial products, salaries of State Civil Apparatus (ASN), and others. Until this research was conducted, BAZNAS of Asahan Regency distributed zakat funds only to four groups of mustahik:the poor, riqab, gharimin, and fi-sabilillah. The zakat collected at BAZNAS Asahan Regency has exceeded the specified target, and is distributed in four patterns of zakat distribution, namely traditional consumptive, creative consumptive, traditional productive, and creative productive. The obstacles faced are the lack of public awareness, lack of regulatory support from the government, and the lack of assistance and guidance to mustahik.